2003
DOI: 10.1073/pnas.0334049100
|View full text |Cite
|
Sign up to set email alerts
|

Working memory and fear conditioning

Abstract: In trace conditioning, a short interval is interposed between the termination of the conditioned stimulus (CS) and the onset of the unconditioned stimulus (US). In delay conditioning, the CS and US overlap. We here investigate the extent to which human classical fear conditioning depends on working memory. Subjects had to carry out an n-back task, requiring tracking an item 1 or 2 back in a sequentially presented list of numbers, while simultaneously being tested for their ability to associate auditory cues wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
113
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(121 citation statements)
references
References 43 publications
8
113
0
Order By: Relevance
“…Similar observations of learning without awareness have been found during Pavlovian fear conditioning (Bechara et al, 1995;Esteves, Parra, Dimberg, & Öhman, 1994;Knight et al, 2003). These studies suggest that contingency awareness does not influence differential CR expression during certain delay procedures , whereas awareness of stimulus relationships appears to facilitate trace fear conditioning and is correlated with CR expression during the extinction of trace conditioned fear (Carter, Hofstötter, Tsuchiya, & Koch, 2003).…”
supporting
confidence: 67%
See 1 more Smart Citation
“…Similar observations of learning without awareness have been found during Pavlovian fear conditioning (Bechara et al, 1995;Esteves, Parra, Dimberg, & Öhman, 1994;Knight et al, 2003). These studies suggest that contingency awareness does not influence differential CR expression during certain delay procedures , whereas awareness of stimulus relationships appears to facilitate trace fear conditioning and is correlated with CR expression during the extinction of trace conditioned fear (Carter, Hofstötter, Tsuchiya, & Koch, 2003).…”
supporting
confidence: 67%
“…SCRs were slightly larger on unperceived trace CS than on unperceived trace CS trials, and perhaps significant differences would have been observed had it not been for other factors that can influence conditioning. For example, trace procedures appear to be more difficult than delay conditioning, and increasing task difficulty often interferes with CR acquisition (Carter et al, 2003;Solomon & Groccia-Ellison, 1996;Thompson, Moyer, & Disterhoft, 1996). In addition, the duration of the trace CS was shortened to maintain the same interstimulus interval between CS onset and UCS presentation for the delay and trace procedures.…”
Section: Discussionmentioning
confidence: 99%
“…In trace cued conditioning, an auditory CS is separated by an interval of time before mice receive a footshock US. Mice acquire a context-US and a CS-US association, but the insertion of a time interval between the CS and US requires working memory to be engaged [15]. Therefore, the hippocampus is required for both the context-US and CS-US associations [114,134].…”
Section: The β2 Nachr Subunitmentioning
confidence: 99%
“…Instead, extinction treatment generates new (inhibitory) context-dependent learning (Bouton, 2002(Bouton, , 2004. In human subjects, concurrent working memory performance interferes with Pavlovian fear conditioning, indicating that fear response acquisition in humans is a learning phenomenon that may also depend on higher-level cognitive processes (Carter et al, 2003). Concurrence of deficits in working memory and conditioned fear extinction in mGluR7 Ϫ/Ϫ mice suggests that suppression of conditioned fear during extinction training may rely on working memory resources, similar to other forms of fear suppression in rats (Beckers et al, 2006).…”
Section: Concurrence Of Working Memory and Extinctionmentioning
confidence: 99%
“…Although the neurobehavioral basis of fear acquisition is well understood (Maren, 2001), less is known about mechanisms underlying extinction (Myers and Davis, 2002). Because extinction is now considered to be an active and context-dependent form of learning inhibiting the expression of conditioned fear responses (Bouton, 2002(Bouton, , 2004Rescorla, 2004), it may depend on higher-level cognitive processes similar to those involved in working memory (Carter et al, 2003).…”
Section: Introductionmentioning
confidence: 99%